Geospatial linked data proliferation in nmcas: systematic literature review - Čeh, Marjan (Geodetski vestnik, 2023)
This research focuses on a systematic literature review of the geospatial Linked Data (LD) publication at National Mapping and Cadastral Agencies in Europe (NMCA) responsible for land administration. We analysed scientific studies published from 2014 to 2023. Our research aimed to find out the reasons for the relatively slow adoption of geospatial data publication as LD. Therefore, we searched for the most common problems, solutions, and challenges for publishing prioritised data themes in NMCAs. Applied research methodology relies on well-established approaches such as analysing Population Problems, Intervention, Comparison, Outcomes, and Circumstances (PICOC) and backward snowballing. The eligibility process is presented by Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. We analysed nineteen extracted papers and identified twelve key issues from fulltext reading. Frequency analyses resulted in the overview of the most frequently published geospatial themes as LD in several European countries. We addressed five research questions and concluded that in addition to systematic support for developing vocabularies and ontologies, trust, awareness, and knowledge about best practices could influence the success of LD publication at NMCAs.
Keywords: geodetske uprave; geoprostorska semantika; geospatial semantics; interoperability; interoperabilnost; linked data; national mapping and cadastral agency; NMCA; povezani podatki; sistematični pregled literature; SLR; Systematic Literature Review